EKSTERNALITAS INDUSTRI BATU BATA TERHADAP SOSIAL EKONOMI DI KECAMATAN TENAYAN RAYA - Vivin Veronika; Nursiah Chalid; Eriyati ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research was conducted in the District Tenayan Raya Pekanbaru, purpose this study was to analyze the industry externalities brick against the District socioeconomic Tenayan Kingdom. With this research is expected to provide assistance and information to masyarakata Pekanbaru city local government in planning the construction industry more environmentally friendly. The method used is simple random sampling method, with a population of 136 716 inhabitants and 44 191 heads of households, 1999 businesses and 64 traditional mechanical effort, and 3809 workers. In this study are all affected communities from the consequences of industrial pengelolahan bricks by sampling with as many as 44 respondents consisting of industry-traditional, mechanical industry, households and population according to labor scattered in villages in the District Tenayan Kingdom, namely the Village Kulim, Tangkerang East Village, Village Rejosari, and the Village Sail. Based on the results of research conducted, it is concluded that the impact of brick industry of the positive side of which is; employment, increase incomes of the population, increasing purchasing power, sufficiency life, being able to buy on credit, growing businesses such as the procurement of firewood , the growth of the property, the proliferation of the store building, the establishment of Credit Unions and as well as the need for transportation. While the negative impacts of industrial production activities on these bricks is a major tissue damage soil, pollution of air pollution, the difficulty of getting clean water, disease suffered by the community, length of illness, medical expenses incurred by the respondent.Keywords : natural resources, externalities, and social economy